From Middle Childhood to Adulthood Attachment: Measuring Attachment Stability in the Context of Married Individuals in Penang, Malaysia. (October 2018) - Mohd Hasim, Marshina Juliza; Mustafa, Hasrina; Hashim, Nor Hazlina
Attachment theory argues that attachment styles developed during infancy and childhood will be relatively enduring and continue during adulthood. While research on adult attachment has been mounting in the past, less is known on the enduring effect of attachment styles with mother, father, and their peer or peers during childhood on adult romantic attachment styles. Past research in fact have obtained mixed findings on the stability of attachment styles from childhood to adulthood, especially in the context of Malaysian setting. In order to explore the stability of attachment styles from childhood to adulthood, a survey among 400 married individuals was conducted and partial least squares was employed for data analysis. The application of attachment theory in this study was established via two dimensions of anxiety and avoidance. The result indicated that respondents who exhibited high levels of anxiety and high levels of avoidance with mother, father, and their peers would display the same attachment styles with their romantic partners or spouses during adulthood. The findings provide conclusive evidence on the continuity and stability of attachment styles with stronger and enduring bonds observed for peer-adult attachment.